Child maltreatment during the COVID-19 pandemic: implications for child and adolescent mental health - McDowell, Hannah; Barriault, Sophie; Afifi, Tracie O.; Romano, Elisa; Racine, Nicole (Frontiers in Child and Adolescent Psychiatry, 2024)
As societies worldwide addressed the numerous challenges associated with the COVID-19 pandemic, a troubling concern emerged—the possible rise of child maltreatment, which is a pernicious risk factor for child and adolescent mental health difficulties. This narrative review aims to provide a comprehensive understanding of how the many changes and challenges associated with the pandemic influenced worldwide occurrences of child maltreatment and, subsequently, the mental health of children and adolescents. First, we present the well-established evidence regarding the impact of child maltreatment on the mental health of children and adolescents both before and during the COVID-19 pandemic. Next, we examine the existing literature on the prevalence of child maltreatment during the pandemic, explanations for conflicting findings, and key mechanisms influencing the prevalence of maltreatment. Using a heuristic model of child maltreatment and its downstream influence on child mental health, we discuss risk and protective factors for maltreatment as well as mechanisms by which maltreatment operates to influence child and adolescent mental health. Finally, based on the accumulated evidence, we provide important recommendations for advancing research on child maltreatment, emphasizing the necessity for routine monitoring of maltreatment exposure at a population level, and discussing the implications for the field of child protection. This comprehensive review aims to contribute to the understanding of the challenges arising from the intersection of the COVID-19 pandemic and child maltreatment, with the goal of informing effective interventions in the domain of child welfare.